2018
DOI: 10.1002/jcla.22629
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long noncoding RNA ANRIL downregulation correlates with increased risk, higher disease severity and elevated pro‐inflammatory cytokines in patients with acute ischemic stroke

Abstract: Circulating lncRNA ANRIL downregulation correlates with increased stroke risk, higher disease severity and elevated inflammation in AIS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 21 publications
(40 reference statements)
0
37
0
Order By: Relevance
“…These studies suggest that lnc-ANRIL overexpression promotes inflammation, while lnc-anril knockdown reduces inflammation and alleviates neuronal injury. Notably, there are also studies illustrating an anti-inflammatory role of lnc-anril in various diseases (10,26). For example, a high expression of lnc-anril was associated with a decreased risk of acute exacerbation, pro-inflammatory cytokine expression and the global initiative for chronic obstructive lung disease stage in patients with chronic obstructive pulmonary disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that lnc-ANRIL overexpression promotes inflammation, while lnc-anril knockdown reduces inflammation and alleviates neuronal injury. Notably, there are also studies illustrating an anti-inflammatory role of lnc-anril in various diseases (10,26). For example, a high expression of lnc-anril was associated with a decreased risk of acute exacerbation, pro-inflammatory cytokine expression and the global initiative for chronic obstructive lung disease stage in patients with chronic obstructive pulmonary disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…Further study showed that ANRIL could enhance the viability of VSMCs via regulating miR-181a/silent information regulator 1 (SIRT1) (65). In addition, ANRIL downregulation correlated with elevated pro-inflammatory cytokines in patients with acute ischemic stroke, indicating ANRIL modulates inflammation (99). It was suggested that ANRIL could promote cholesterol efflux and inhibit inflammatory cytokines such as IL-1β and TNF-α in ox-LDL-exposed THP-1 macrophages by silencing ADAM (a disintegrin and metalloprotease) 10 (66).…”
Section: Anril (Cdkn2b-as1)mentioning
confidence: 98%
“…Numerous studies showed that lncRNAs are related to neuroinflammation and the activation of microglia in ischemic stroke. It was reported that the expression of lncRNA ANRIL was negatively associated with hs-CRP, TNF-α, and IL-6 levels, but positively correlated with IL-10 levels in AIS patients, suggesting that lncRNA ANRIL play an anti-inflammatory role in AIS progression (Feng et al, 2019). A recent study found that knockdown of lncRNA MALAT1 attenuated the inflammatory injury after brain ischemia, whereas overexpression of MALAT1 exacerbated ischemic brain inflammation (Cao et al, 2020).…”
Section: Lncrnas and Neuroinflammationmentioning
confidence: 99%